Engineered Axonal Tracts as "Living Electrodes" for Synaptic‐Based Modulation of Neural Circuitry. (4th September 2017) - Serruya, Mijail D.; Harris, James P.; Adewole, Dayo O.; Struzyna, Laura A.; Burrell, Justin C.; Nemes, Ashley; Petrov, Dmitriy; Kraft, Reuben H.; Chen, H. Isaac; Wolf, John A.; Cullen, D. Kacy
Abstract: Brain–computer interface and neuromodulation strategies relying on penetrating non‐organic electrodes/optrodes are limited by an inflammatory foreign body response that ultimately diminishes performance. A novel "biohybrid" strategy is advanced, whereby living neurons, biomaterials, and microelectrode/optical technology are used together to provide a biologically‐based vehicle to probe and modulate nervous‐system activity. Microtissue engineering techniques are employed to create axon‐based "living electrodes", which are columnar microstructures comprised of neuronal population(s) projecting long axonal tracts within the lumen of a hydrogel designed to chaperone delivery into the brain. Upon microinjection, the axonal segment penetrates to prescribed depth for synaptic integration with local host neurons, with the perikaryal segment remaining externalized below conforming electrical–optical arrays. In this paradigm, only the biological component ultimately remains in the brain, potentially attenuating a chronic foreign‐body response. Axon‐based living electrodes are constructed using multiple neuronal subtypes, each with differential capacity to stimulate, inhibit, and/or modulate neural circuitry based on specificity uniquely afforded by synaptic integration, yet ultimately computer controlled by optical/electrical components on the brain surface. Current efforts are assessing the efficacy of this biohybrid interface for targeted, synaptic‐based neuromodulation, and the specificity, spatial density and long‐term fidelity versus conventional microelectronic or optical substrates alone. Abstract : A biohybrid brain–machine interface strategy is developed using neuron/axon‐based "living electrodes" within microcolumnar encasement. The perikaryal segment remains quasi‐externalized under optical/electrical arrays on a brain surface, while the axonal segment is microinjected for targeted, synaptic‐based neuromodulation of deep host circuitry. This biohybrid approach is at the intersection of neuroscience and engineering to establish biological intermediaries between man and machine.